The role of economic growth in cultural development during the period of accelerated industrialization and modernization - the case of Ho Chi Minh City, Vietnam - Thi Bich Tram, Phan (Edelweiss Applied Science and Technology, 2024)
During the period of accelerated industrialization and modernization, with the combination of talent and relentless efforts from the Party Committee, the Government, and the people, Ho Chi Minh City has become a key economic region in the South and across the country. However, alongside the remarkable successes in economic growth, many challenges have also arisen concerning cultural, environmental, and social issues. Therefore, managing economic growth in a balanced, sustainable, and harmonious manner with cultural development has become an urgent task during the phase of intensified industrialization and modernization in Ho Chi Minh City. This article will analyze the current role of economic growth in cultural development during the period of accelerated industrialization and modernization in Ho Chi Minh City. From there, the article will propose several orientations and solutions to enhance the role of economic growth in cultural development, aiming to ensure balance and comprehensive development for Ho Chi Minh City.